EXPLORING EFL STUDENTS' LEARNING STRATEGIES AND THEIR ONLINE LEARNING ENGAGEMENTS AMID COVID-19 PANDEMIC - Dimas Mulia; Ive Emaliana (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2021)
Amid Covid-19 pandemic, emergency remote teaching has been done through online learning. Recent research has found some challenges and opportunities, including the debate analyzing the effectiveness of EFL online teaching and learning processes. However, little is known about the types of learning strategies that suit students' engagement with online learning. The investigation between them illustrates an emerging paradigm for English learning in an online setting, where learning takes place in authentic environments with immersive experiences in order to achieve meaningful learning. This early examination reveals assessments on their natures and applications in connection to English success with the goal of distributing such a revolutionary arena. The findings are revealed in the conclusions in the form of model hypothesis of causal relationship may accordingly help other researchers to conduct further research in exploring the prediction of learning strategies provided in this paper when dealing with enhancing EFL teaching method during this emergency remote teaching and learning